Legal Review Of Plastic Waste Handling For Streetfood Businesses - Abim Dwi Nugroho; Dianita Utami; Zahran Muhammad Ikhwan; Endang Sutrisno; Harmono Harmono (Journal Of Social Science (JoSS), 2024)
Plastic waste is still a problem that is difficult to solve due to the lack of awareness about the importance of keeping the environment clean and not leaving litter lying around. Usually, waste generation is generated by economic activities and has the potential to cause environmental pollution. In Cirebon City itself, plastic waste is still an unresolved problem. With the increase in population, there will be an increase in the volume of waste generated by human activities. The problem is how the Cirebon city local government policy related to handling plastic waste generated by street food business actors, this is intended to examine the regulations that have been implemented and run in the city of Cirebon, with an empirical juridical research approach and qualitative data included. This study aims to determine the procedure for handling plastic waste and the elements that influence plastic waste management in the city of Cirebon. Also to find out what anticipatory steps need to be taken in the future.